2024
DOI: 10.2174/2772432817666220607114559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drugs and Chemotherapeutic Agents on Dental Implant Osseointegration: A Narrative Review

Abstract: Background: Dental implants have been one of the most popular treatments for rehabilitating individuals with single missing teeth or fully edentulous jaws since their introduction. As more implant patients are well-aged and take several medications due to various systemic conditions, clinicians should be mindful of possible drug implications on bone remodeling and osseointegration. Objective: The present study aims to study and review some desirable and some unwelcomed implications of medicine on osseointeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 189 publications
0
3
0
Order By: Relevance
“…In addition, PRF was used by others to prevent MRONJ due to the high concentration of platelet‐derived growth factors (PDGF), which plays a crucial role as an essential regulator for the migration, proliferation, and survival of mesenchymal cells. In addition, PRF contains transforming growth factor‐β1, a growth factor that is released by autologous bone, which stimulates synthesis of type 1 collagen and fibronectin and vascular endothelial growth factor (VEGF), the most potent growth factor leading to tissue angiogenesis (Mohammadi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PRF was used by others to prevent MRONJ due to the high concentration of platelet‐derived growth factors (PDGF), which plays a crucial role as an essential regulator for the migration, proliferation, and survival of mesenchymal cells. In addition, PRF contains transforming growth factor‐β1, a growth factor that is released by autologous bone, which stimulates synthesis of type 1 collagen and fibronectin and vascular endothelial growth factor (VEGF), the most potent growth factor leading to tissue angiogenesis (Mohammadi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some therapeutic protocols have been proposed to enhance the healing and the predictability of the surgical treatment, such as ozone therapy (Ripamonti et al, 2011 ), low‐level laser therapy (Sarkarat et al, 2019 ; Scoletta et al, 2010 ), hyperbaric oxygen (Freiberger et al, 2012 ), autologous platelet concentrates (APCs) (Adornato et al, 2007 ; Del Fabbro et al, 2018 ; Miranda et al, 2021 ; Sarkarat et al, 2014 ) and combination therapies (Sarkarat et al, 2022 ). The combination of the surgical treatment and autologous membranes of platelet‐rich fibrin (PRF) has the objective of adding bioactive factors to the surgical site to accelerate bone and soft tissue healing (Adornato et al, 2007 ; Mohammadi et al, 2022 ; Nørholt & Hartlev, 2016 ; Sabri et al, 2022 ). Recent systematic reviews on this topic have concluded that there is still insufficient evidence to prove the true benefits of platelet concentrates in the healing of ONJ lesions (Fabbro et al 2015 , 2018 ; Fortunato et al, 2020 ; Lopez‐Jornet et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review revealed that non-steroidal anti-inflammatory drugs, glucocorticoids, proton pump inhibitors, selective serotonin reuptake inhibitors, anticoagulants, metformin, and chemotherapeutic agents may jeopardize osseointegration and lead to implant failure. However, validation is mandatory from human studies with high evidence [24].…”
Section: Discussionmentioning
confidence: 99%